2022
DOI: 10.1007/s11104-022-05426-0
|View full text |Cite
|
Sign up to set email alerts
|

Soil N2O and CH4 emissions from fodder maize production with and without riparian buffer strips of differing vegetation

Abstract: Purpose Nitrous oxide (N2O) and methane (CH4) are some of the most important greenhouse gases in the atmosphere of the 21st century. Vegetated riparian buffers are primarily implemented for their water quality functions in agroecosystems. Their location in agricultural landscapes allows them to intercept and process pollutants from adjacent agricultural land. They recycle organic matter, which increases soil carbon (C), intercept nitrogen (N)-rich runoff from adjacent croplands, and are seasonall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…The emissions of N 2 O and CO 2 have been studied within different riparian buffer vegetations (Baskerville et al, 2021 ; Silverthorn & Richardson, 2021 ), but a direct comparison of these with gases emitted by the agricultural fields they serve remains elusive (Davis et al, 2019 ). In field studies, Davis et al ( 2019 ), Dlamini, Cardenas, Tesfamariam, Dunn, et al ( 2022 ), and Iqbal et al ( 2015 ) found greater N 2 O fluxes from a cropland compared with adjacent riparian buffers as a result of nitrogen fertilization while the riparian buffers were not directly fertilized. In contra, Kim et al ( 2009 ) and Mafa‐Attoye et al ( 2020 ) reported larger N 2 O fluxes from riparian buffers as a result of their greater soil moisture retention compared with the adjacent croplands.…”
Section: Introductionmentioning
confidence: 99%
“…The emissions of N 2 O and CO 2 have been studied within different riparian buffer vegetations (Baskerville et al, 2021 ; Silverthorn & Richardson, 2021 ), but a direct comparison of these with gases emitted by the agricultural fields they serve remains elusive (Davis et al, 2019 ). In field studies, Davis et al ( 2019 ), Dlamini, Cardenas, Tesfamariam, Dunn, et al ( 2022 ), and Iqbal et al ( 2015 ) found greater N 2 O fluxes from a cropland compared with adjacent riparian buffers as a result of nitrogen fertilization while the riparian buffers were not directly fertilized. In contra, Kim et al ( 2009 ) and Mafa‐Attoye et al ( 2020 ) reported larger N 2 O fluxes from riparian buffers as a result of their greater soil moisture retention compared with the adjacent croplands.…”
Section: Introductionmentioning
confidence: 99%
“…Among these gases, CH4 is of particular concern, being the second most important contributor to radiative forcing after CO2 (Cassia et al, 2018). It possesses a significantly higher global warming potential, with a 100-year warming potential approximately 28 times that of CO2 (Dlamini et al, 2022). Agricultural practices, especially in rice paddies, have been identified as substantial sources of CH4 and N2O emissions.…”
Section: Introductionmentioning
confidence: 99%